Empowering Loan Awareness: The Role of Sharī‘ah Financial Literacy, Blockchain, and Fintech Trust - Sumar'in, Sumar'in; Ardi, Pahmi; Sumin, Sumin; Kusnadi, Iwan (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2025)
Research Originality. Despite extensive research on Sharī‘ah financial literacy and fintech trust, their combined impact on illegal loan awareness remains unexplored. This study bridges that gap by analyzing their interaction in financial decision-making amid rising predatory lending, offering a novel perspective on their protective role against unethical financial practicesResearch Objectives. This study aims to examine the effect of Sharī‘ah financial literacy on awareness of illegal online loans, with blockchain technology understanding and Sharī‘ah fintech trust as mediating variables.Research Methods. An associative quantitative approach was employed, utilizing a survey of 519 Indonesian millennial Muslims, selected through simple random sampling. Data analysis was conducted using structural equation modeling (SEM) to explore the relationships among variables.Empirical Results. The findings indicate that Sharī‘ah financial literacy significantly influences blockchain understanding, fintech trust, and awareness of illegal online loans. Blockchain understanding enhances fintech trust but does not directly impact loan awareness, whereas trust in Sharī‘ah fintech positively affects awareness of illegal online lending risks.Implications. This study underscores the importance of improving Sharī‘ah financial literacy and blockchain understanding to strengthen consumer trust in Sharī‘ah fintech and raise awareness of illegal online lending risks. However, further research with broader samples is recommended to validate these findings.JEL Classification: G41, G28, O33, Z12, D83How to Cite:Sumar’in, Ardi. P, Sumin, & Kusnadi, I. (2025). Empowering Loan Awareness: The Role of Sharī‘ah Financial Literacy, Blockchain, and Fintech Trust. Signifikan: Jurnal Ilmu Ekonomi, 14(1), 179-196. https://doi.org/10.15408/sjie.v14i1.44735.